2007
DOI: 10.1071/ar06203
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of malting quality traits in two barley populations

Abstract: Selection for malting quality traits is a major breeding objective for barley breeding programs. With molecular markers linked to loci affecting these traits, this selection can be undertaken at an earlier stage of the breeding program than is possible using conventional tests. Quantitative trait loci (QTLs) associated with malting quality traits were mapped in 2 populations derived from parents with elite malting quality. Progeny from an Arapiles/Franklin population grown in 4 environments and an Alexis/Sloop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 24 publications
4
53
0
Order By: Relevance
“…It was reported that the SSR marker EBmac0501 on chromosome 1H was associated with malt extract (Zale et al, 2000;Hoffman and Dahleen, 2002;Emebiri et al, 2004;Panozzo et al, 2007). In our study, the results generated from genotyping of EBmac0501 indicated that eight malting barley varieties 'Yangnongpi 4', 'Amaji Nijo', 'Daner', 'ZJU 8', 'Supi 3', 'Zhepi 8', 'Hua 30', and 'Xiumai 3' showed the same allele.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It was reported that the SSR marker EBmac0501 on chromosome 1H was associated with malt extract (Zale et al, 2000;Hoffman and Dahleen, 2002;Emebiri et al, 2004;Panozzo et al, 2007). In our study, the results generated from genotyping of EBmac0501 indicated that eight malting barley varieties 'Yangnongpi 4', 'Amaji Nijo', 'Daner', 'ZJU 8', 'Supi 3', 'Zhepi 8', 'Hua 30', and 'Xiumai 3' showed the same allele.…”
Section: Discussionsupporting
confidence: 48%
“…SSR markers, an excellent molecular marker system with the advantages of being codominant, abundant, highly reproducible, highly polymorphic, and easy to assay, have been used in many types of genetic analyses such as the construction of linkage maps, diversity assessment of germplasm, and identification of molecular markers for marker-assisted selection (Matus and Hayes, 2002;Marcel et al, 2007;Pushpendra et al, 2007). Quantitative trait locus (QTL) analysis of malting quality has been performed in recent years on a number of crosses derived from different germplasm sources originating from North America, Europe, and Australia, and significant advances in knowledge have been achieved (Zale et al, 2000;Hoffman and Dahleen, 2002;Li et al, 2003;Emebiri et al, 2004;Marcel et al, 2007;Panozzo et al, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…The present study demonstrated that there was small difference of the closest linked markers for different traits in the traditional QTL region for malting quality Li et al 2003Li et al , 2005Mather et al 1997;Marquez-cedillo et al 2000;Panozzo et al 2007;Von Korff et al 2008) when more molecular markers were mapped in the chromosome region. The results in Table 3 indicate that there exist multi-locus clusters for different quality traits in this chromosome region.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous genes and QTL have been identified that are related to malting quality and these have been reviewed by various authors (Kleinhofs and Han 2002;Fox et al 2003;Li et al 2009). Although there was strong QTL × E interaction for the malting quality traits (Panozzo et al 2007), the terminal region of chromosome 5HL has been consistently detected to control multiple malting quality traits (Mather et al 1997;Marquez-Cedillo et al 2000;Collins et al 2003;Li et al 2003;Hayes et al 2003;Li et al 2005;Panozzo et al 2007;Von Korff et al 2008). These traits included malt extract, diastatic power, free amino acid nitrogen, soluble nitrogen, alpha-amylase activity, wort viscosity, beta-glucan and beta-glucanase.…”
Section: Introductionmentioning
confidence: 99%
“…It can account for both intra-and inter-trial variability in the estimation of QTL effects and trait values prediction (Van Eeuwijk et al, 2010). Mixed models have been extensively applied in many QTL mapping settings (Anhalt et al, 2009;Boer et al, 2007;Hackett et al, 2001;Klasen et al, 2012;Korte et al, 2012;MacMillan et al, 2006;Malosetti et al, 2008;Malosetti et al, 2006;Malosetti et al, 2004;Panozzo et al, 2007;Piepho, 2000;Verbyla et al, 2003;Xu, 2013), ranging from single trait single environment analysis up to the most complex setting of multi-trait multi-environment (MTME) with various interactions (traits, environments and/or environmental characterizations).…”
Section: Introductionmentioning
confidence: 99%